Increased saccadic latency in Amblyopia: Oculomotor and attentional factors. (August 2022) - Chow, Amy; Nallour Raveendran, Rajkumar; Erkelens, Ian; Babu, Raiju; Thompson, Benjamin
Abstract: Amblyopia is a neurodevelopmental disorder of vision that arises from disrupted binocular vision during early childhood. Delayed initiation of saccadic eye movements is an established feature of amblyopia. The present study investigated whether oculomotor and/or attentional factors contribute to increased amblyopic eye saccadic latencies. Participants with normal vision (n = 10) and amblyopia (n = 10; 4 anisometropia, 6 strabismic/mixed) performed visually-guided saccades to targets presented via a mirror haploscope. Eye movements were recorded for both eyes even under monocular viewing conditions. In Experiment 1, we measured the latency, amplitude gain and peak velocity of saccades as targets were presented binocularly, or monocularly. Saccadic latencies were significantly longer for both eyes when targets were presented to only the amblyopic eye compared to all other conditions. Saccade gain and main sequence rate constants were similar across groups for all viewing conditions. In Experiment 2, we tested the hypothesis that shifts of overt attention may be deficient when viewing with the amblyopic eye. We presented the fixation target to one eye and the subsequent peripheral target (saccadic error signal) to the other eye. Shifting saccadic targets between the eyes expedited saccadic latencies irrespective of which eye viewed the target in the amblyopia group. These findings indicate that oculomotor factors related to saccade generation are unlikely to be responsible for amblyopic eye saccadic latency delays. We propose that an impairment in the ability to disengage attention from a fixation target and orient to a peripheral target when both targets are seen by the amblyopic eye may contribute to increased saccadic latency.